Guaraná (Paullinia cupana) by‐product as a source of bioactive compounds and as a natural antioxidant for food applications. Issue 10 (9th August 2021) - Pinho, Lorena Silva; da Silva, Marluci Palazzolli; Thomazini, Marcelo; Cooperstone, Jessica L.; Campanella, Osvaldo H.; da Costa Rodrigues, Christianne Elisabete; Favaro‐Trindade, Carmen Sílvia
Abstract: This study aimed to evaluate the extraction and the potential of guaraná peels extract as a source of bioactive compounds and as a natural antioxidant. Guaraná peels were characterized, and different solvents and conditions of extraction were assessed using a full‐factorial design. The total carotenoids content was 65.9 ± 0.4 µg/g, and the major species were β ‐ carotene and lutein. It also presented 0.60 ± 0.01 and 0.55 ± 0.01 mg/g of caffeine and theobromine, respectively. The ability to extract carotenoids followed the increasing order: hexane < ethanol < ethyl acetate < ethanol: hexane < ethanol: ethyl acetate. Carotenoid recovery increased significantly ( p < .05) at 50°C, and the extraction yield was higher over time. ABTS (60 ± 2 µmol Trolox eq./g) and ORAC (76 ± 3 µmol Trolox eq./g) assays indicated that guaraná peels extract has valuable potential for application as an antioxidant in food products. Novelty impact statement: Guaraná peels are underutilized by‐products that the food and pharmaceutical industries in South America could employ in the formulation of many of their products. Guaraná peels are a source of some macro and micronutrients, caffeine, theobromine, phenolic compounds, and carotenoids, all‐ trans ‐β‐carotene, cis ‐β‐carotene, and lutein. The ability to extract carotenoids was evaluated through the screening of potentially suitable solvents, as well as the extraction time and temperature. The suitability of the solvent considered the safety and toxicity of the obtained extracts and the solvent's impact on the environment. The measured antioxidant capacity of guaraná peels extracts indicated its potential valorization by using a green solvent. To the best of our knowledge, no information has been reported concerning the full characterization and chemical origin of guaraná peels pigments, which also provides a prospective multipurpose for application in functional foods.